Development of tools for soil erosion risk mapping for Malaysian forest catchments - Khalit, Saiful Iskandar (2012)
Logging, road construction and heavy machine usage in forest activities are challenges faced when trying to minimize the impact on forest environment,especially land degradation and soil erosion and also contamination of water resources. Measurement of soil loss using a conventional method is time- consuming and expensive. Another problem posed by soil erosion during rainy season, flood occurred at the downstream at Kampung Pasir Raja and settle up the formation of sediment in the river which engaged with public concern. Climatic data was obtained by installation of Automatic Weather Station (AWS) which was carried out from August 2007 to August 2008 (water year cycle) to record daily data. A parameter modification was made to the modified soil loss equation (MSLE) which consisted of rainfall (R), soil erodibility (K), slope length (LS) and vegetation management (VM). This leads to an application of the MSLE which produces a soil erosion maps. The validation of the model is acceptable since the P-value in the ANOVA table is less than 0.01, there is a statistically significant relationship between the variables more than 90 percent (%) confidence level in the STATGRPHICS Plus analysis. In other hands, the validation also was done for two different sites at Blok 5 PITC, Temengor Forest Reserve, Grik, Perak and Bukit Tarek Forest Reserve.